Extreme planet: exploring the most extreme stuff on earth - Dubois, Michael (Australia: Lonely Planet, 2012)
A whirlwind tour of the globe, seeking out the highest, deepest, wildest, thinnest. coolest. hottest, scariest, smelliest... things on the planet. What's the longest place name? The oldest vomit? Most treacherous road in the world and why? Most dangerous food to eat? Scariest place to stand because you're most likely to be struck by lightning? It's all here!
Includes index.